Correlative analysis of immunoreactivity in confocal laser-scanning microscopy and scanning electron microscopy with focused ion beam milling - Sonomura, Takahiro; Furuta, Takahiro; Nakatani, Ikuko; Yamamoto, Yo; Unzai, Tomo; Matsuda, Wakoto; Iwai, Haruki; Yamanaka, Atsushi; Uemura, Masanori; Kaneko, Takehsi (Frontiers in Neural Circuits, 2013)
Three-dimensional reconstruction of ultrastructure of rat brain with minimal effort has recently been realized by scanning electron microscopy combined with focused ion beam milling (FIB-SEM). Because application of immunohistochemical staining to electron microscopy has a great advantage in that molecules of interest are specifically localized in ultrastructures, we here tried to apply immunocytochemistry to FIB-SEM and correlate immunoreactivity in confocal laser-scanning microcopy (CF-LSM) with that in FIB-SEM. The dendrites of medium-sized spiny neurons in rat neostriatum were visualized with a recombinant viral vector, which labeled the infected neurons with membrane-targeted GFP in a Golgi stain-like fashion, and thalamostriatal afferent terminals were immunolabeled with Cy5 fluorescence for vesicular glutamate transporter 2 (VGluT2). After detecting the sites of terminals apposed to the dendrites in CF-LSM, GFP and VGluT2 immunoreactivities were further developed for electron microscopy by the immunogold/silver enhancement and immunoperoxidase/diaminobenzidine (DAB) methods, respectively. In the contrast-inverted FIB-SEM images, silver precipitation and DAB deposits were observed as fine dark grains and diffuse dense profiles, respectively, indicating that these immunoreactivities were easily recognizable as in the images of transmission electron microscopy. In the sites of interest, some appositions were revealed to display synaptic specialization of asymmetric type. The present method is thus useful in the three-dimensional analysis of immunocytochemically differentiated synaptic connection in the central neural circuit.